2021
DOI: 10.1126/sciadv.abh3674
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the first global population estimate of Weddell seals in Antarctica

Abstract: The Weddell seal is one of the best-studied marine mammals in the world, owing to a multidecadal demographic effort in the southernmost part of its range. Despite their occurrence around the Antarctic coastline, we know little about larger scale patterns in distribution, population size, or structure. We combined high-resolution satellite imagery from 2011, crowd-sourcing, and habitat modeling to report the first global population estimate for the species and environmental factors that influence its distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 77 publications
2
26
0
Order By: Relevance
“…Satellite images can provide extensive coverage, enabling even continental-scale counts to use for abundance and distribution estimations in remote locations ( e.g. , LaRue et al, 2019 ; LaRue et al, 2020 ; LaRue et al, 2021 ), making sampling efforts more globally even. Although UAS provide less spatial coverage than satellite images, they can allow more control over survey timing and surveying in overcast conditions, as well as higher spatial resolution, which can be of use for smaller marine mammals like sea otters ( Enhydra lutris ) or dolphins of the Cephalorhynchus genus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite images can provide extensive coverage, enabling even continental-scale counts to use for abundance and distribution estimations in remote locations ( e.g. , LaRue et al, 2019 ; LaRue et al, 2020 ; LaRue et al, 2021 ), making sampling efforts more globally even. Although UAS provide less spatial coverage than satellite images, they can allow more control over survey timing and surveying in overcast conditions, as well as higher spatial resolution, which can be of use for smaller marine mammals like sea otters ( Enhydra lutris ) or dolphins of the Cephalorhynchus genus.…”
Section: Discussionmentioning
confidence: 99%
“…While satellite images have allowed continental-scale abundance and distribution studies in remote locations ( e . g. , LaRue et al, 2019 ; LaRue et al, 2020 ; LaRue et al, 2021 ), that work required crowdsourcing: LaRue et al (2020) enlisted more than 325,000 volunters to analyze 268,611 km 2 of images while a previous effort ( LaRue et al, 2019 ) used more than 5,000 volunteers for the Ross Sea region in Antarctica. These broad-scale studies remain scarce for marine mammals: most work based on satellite images is performed over smaller areas such as individual islands (e.g., LaRue et al, 2015 ; LaRue & Stapleton, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the seals, many surveys have been conducted using snowmobiles [30,58]. Recently, this effort has been made easier through the use of high-resolution satellite imagery and aerial vehicle (e.g., drones) techniques pioneered and instituted by U.S. scientists [58][59][60][61]. The importance of such population monitoring is enhanced by coincident demographic and foraging behavior studies that indicate the possible causes and effects of observed changes in the sizes, age/sex compositions, and productivity of these indicators of systemic changes (e.g., [52,62,63]).…”
Section: Summary Of United States Ross Sea Researchmentioning
confidence: 99%
“…The iconic Weddell seal ( Leptonychotes weddellii ) is the southernmost breeding mammal in the planet, requiring Antarctica’s fast-ice habitat for reproduction. Despite intense biological and ecological investigation, much of the research effort for the species was in the Ross Sea (Goetz et al 2017; Rotella et al 2012), and recent research suggests the presence of the species in the Amundsen Sea to be relatively low when compared to the rest of the continent (LaRue et al 2021). Mapping of Weddell seal local (Figure 10 in Bengtson et al 2011) and circumpolar (Figure 1 in (LaRue et al 2021) distribution even indicate the species to be absent in the eastern limit of the Amundsen Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intense biological and ecological investigation, much of the research effort for the species was in the Ross Sea (Goetz et al 2017; Rotella et al 2012), and recent research suggests the presence of the species in the Amundsen Sea to be relatively low when compared to the rest of the continent (LaRue et al 2021). Mapping of Weddell seal local (Figure 10 in Bengtson et al 2011) and circumpolar (Figure 1 in (LaRue et al 2021) distribution even indicate the species to be absent in the eastern limit of the Amundsen Sea. Access to that area for in situ observations can be difficult due to persistent floating ice cover (Hogan et al 2020), a constrain that telemetry tagging of seals can help overcome.…”
Section: Introductionmentioning
confidence: 99%